(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article discusses the etiology, pathogenesis, clinical features, diagnostic methods, and modern treatment approaches of bronchial asthma. Bronchial asthma is a chronic inflammatory disease of the airways with an increasing global prevalence. Special attention is paid to early diagnosis, individualized treatment strategies, and improving patients’ quality of life.